PENGARUH LEADERSHIP TRANSFORMASIONAL ATAS ORGANIZATIONAL CITIZENSHIP BEHAVIOR KEPADA KARYAWAN DAN DOSEN FUAD IAIN CURUP - Pefriyadi, Pefriyadi; Alparedi, Topan (Universitas Prof. Dr. Hazairin SH, 2023)
The purpose of this study was carried out to see the effect of transformational leadership on organizational citizenship behavior on Employees and Lecturers at faculty of Ushuluddin, Adab, Da'wah (FUAD) IAIN Curup. The subjects used in this study were 52 employees and lecturers at FUAD IAIN Curup. In this study a quantitative design was used while the design in data collection carried out a questionnaire with five Likert scales of transformational leadership on organizational citizenship behavior. The analysis design used in this study is to use a simple linear regression test. The conclusion of this study shows that there is a positive impact of transformational leadership on organizational citizenship behavior of 11.035% for the employees and lecturers of FUAD IAIN Curup. The implication of this study is to increase understanding of the influence of transformational leadership.